Some uses of subject-side assessments. (October 2017) - Edwards, Derek; Potter, Jonathan
We focus on assessments in conversation, paying particular attention to a distinction between object-side (O-side) and subject-side (S-side) assessments. O-side assessments are predicated of an object (that it is good, awful, nice, bad, etc.), whereas S-side assessments formulate a disposition of the speaker toward that object (that they like it, love it, hate it, cannot stand it, etc.). Despite looking somewhat interchangeable, logically, these different ways of making assessments serve different interactional functions. In particular, S-side assessments allow for contrasting assessments of the same object by different persons. They are therefore useful in the management and avoidance of conflict and misalignment in the performance of actions such as compliment receipts, avoiding giving offense and disagreeing. We link the analysis to conversation analytic work on assessments and to discursive psychology's focus on the everyday management of relations between mental states and an external world.